The Sustainable interior design for design halls in art faculties to face climate change in the twenty-first century - . Noha Mohamed Reda Elsayed Ibrahim; Prof. Dr. Ali Abdel Moneim Shams; Prof. Dr. Ashraf Hussein Ibrahim (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2023)
The twentieth century is considered one of the most important centuries that witnessed a development in the field of discoveries and inventions in human history and the transition of science from the industrial age to the information age, In addition to the tremendous digital technological development witnessed in the first and second decades of the twenty-first century. Here, the importance of sustainable interior design for design halls in art faculties appears because of its fundamental impact on the integration and harmony of design with the surrounding environment to face the effects of climate change by focusing on achieving environmental, economic and social standards using plant elements, and designs that support a range of functions through Reconfiguration , and computer programs to face climate fluctuations and reduce the consumption of non-renewable energy.Therefore, the existing art faculties need to develop their capabilities to keep pace with the new educational systems with continuous development at the design and technical levels, to take advantage of the successive developments in information technology, and to prepare a graduate who meets the requirements of local and international work to support future job opportunities for him.To reach this aim, the research addresses the following points:1. The impact of sustainable design standards on the development of design halls in art faculties.2. Presenting a future vision for the development of design halls to achieve sustainable design.The research ends with a set of important results and recommendations in the field of interior design, and sustainability.